Simulation optimization for the stochastic economic lot scheduling problem with sequence-dependent setup times - Löhndorf, Nils; Riel, Manuel; Minner, Stefan (International journal of production economics, 2014)
We consider the stochastic economic lot scheduling problem (SELSP) with lost sales and random demand where switching between products is subject to sequence-dependent setup times. We propose a solution based on simulation optimization using an iterative two-step procedure which combines global policy search with local search heuristics for the traveling salesman sequencing subproblem. To optimize the production cycle, we compare two criteria: minimizing total setup times and evenly distributing setups to obtain a more regular production cycle. Based on a numerical study, we find that a policy with a balanced production cycle leads to lower cost than other policies with unbalanced cycles. •This paper analyzes the stochastic economic lot-scheduling problem with sequence dependent setup times.•A simulation optimization methodology is presented.•The proposed policy with balanced setups for the products outperforms other fixed-cycle policies.